2019
DOI: 10.1063/1.5107460
|View full text |Cite
|
Sign up to set email alerts
|

Real-time dynamic holographic display realized by bismuth and magnesium co-doped lithium niobate

Abstract: Particular attention has been given to updatable or dynamic holographic displays in recent years. The absence of ideal recording materials hampered the realization of their commercial applications. A lithium niobate crystal codoped with 1.0 mol. % bismuth and 6.0 mol. % magnesium has been grown with a diameter of 2-in. A moderately large saturation diffraction efficiency of 26% can be achieved, which corresponds to a refractive index change of 2.45 × 10−5. However, the photorefractive response time turns out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
12
0
2
Order By: Relevance
“…The response time for LN6 (LN:V,Zr 4.0 ) is 1.1 s and 2.0 s at 488 nm and 532 nm, respectively. It is not as short as mono vanadium-doped LN (LN8), but it is still two orders shorter than CLN and LN:Fe and is one order shorter compared to LN:Mg,Fe, and is also a fraction shorter than LN7 at 532 nm and 488 nm, respectively [23,24,25,26,28]. The LN7 (LN:V,Fe) crystal enjoys higher diffraction efficiency at 532 nm and 488 nm compared to LN1-LN6, LN8, CLN, LN:Zr,Fe, and LN:Mg,Fe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The response time for LN6 (LN:V,Zr 4.0 ) is 1.1 s and 2.0 s at 488 nm and 532 nm, respectively. It is not as short as mono vanadium-doped LN (LN8), but it is still two orders shorter than CLN and LN:Fe and is one order shorter compared to LN:Mg,Fe, and is also a fraction shorter than LN7 at 532 nm and 488 nm, respectively [23,24,25,26,28]. The LN7 (LN:V,Fe) crystal enjoys higher diffraction efficiency at 532 nm and 488 nm compared to LN1-LN6, LN8, CLN, LN:Zr,Fe, and LN:Mg,Fe.…”
Section: Resultsmentioning
confidence: 99%
“…To realize a nonvolatile readout, several methods have been developed so far, i.e., thermal fixing, electrical fixing, and two-step recording [14,22]. Though, up to now, there is good improvement in the response speed of the various doped LN crystals [23,24,25,26], much research is needed to get a practical fast responsive material with a high diffraction efficiency. Recently it was found that vanadium doping in LN elicited shortening of the response time [18,19,26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem at the time was the small size of the crystals (about , which limited the extent of the image that could be displayed. It has to be noted that there are still some efforts in that direction by growing larger crystals (up to ) of bismuth and magnesium co-doped lithium niobate [ 83 ].…”
Section: Photorefractive-based 3d Displaymentioning
confidence: 99%
“…Here, there are two reasons why we select Zr 4+ and Mg 2+ ions as double-doping candidates in LN. First, Mg 2+ is widely used as a primary additive co-doping with other dopants in LN to precisely regulate optical properties and defect structures, such as LN:Mg,Bi [15] and LN:Mg,Zn [16]. These reports provided us with ideas to lower the phase-matching temperature while maintaining the optical damage resistance in LN.…”
Section: Introductionmentioning
confidence: 99%